Be(com)ing: Humankind as Gift and Call - Olthuis, James H. (Philosophia reformata, 1993)
Fifty-eight years ago Max Scheler, one of the founders of modern philosophical anthropology, wrote: “Man is more of a problem to himself at the present time than ever before in all recorded history. ... the increasing multiplicity of the special sciences that deal with man, valuable as they are, tend to hide his nature more than they reveal it.”1 In 1944, some sixteen years later, Ernst Cassirer comments that even though “no former age was ever in such a favorable position with regard to the sources of our knowledge of human nature,” we are still looking for a clue which will provide “real insight into the general character of human culture.”2 In his famous 1958 book, Irrational Man,3 William Barrett looked to existentialism to recover the whole and integral, suffering and dying human being from the abstract image of humankind as logical operators dominant in modern philosophy. However, in a new book William Barrett concludes that the concrete human self was not in fact recovered in existentialism and laments its disappearance in modern thought. He talks of the Death of the Soul.4 I would add: and Elimination of the Body.